The Adjacency Pairs in EFL Virtual Classes: A Conversation Analysis - Fajar, Syams; Arrasyid, Farouk Imam; Rizka, Haira (STIT Buntet Pesantren Cirebon, 2023)
There are many variations in the conversation between students and lecturers. The conversation between those two parties in classroom tend to be in one way or teacher-centered. This study employs conversation analysis of adjacency pairs. There have been many studies that analysis the use of adjacency pairs in a conversation, but there are no ones that focus on virtual platform. This study aims to find out adjacency pairs in conversations between a lecturer and students in the EFL virtual class. In conducting the study, researchers employed qualitative research method. The data used in this study were words in the form of recordings from virtual meetings at the EFL speaking virtual class at IAIN Syekh Nurjati Cirebon. The recording was transcribed and the data were analyzed using textual analysis. The finding of this research shows 12 adjacency pairs that emerge from the conversation. Finally, this study can be a practical guidliness for teachers, lecturers, and students who are interested in type of adjacency pairs and communicative functions in EFL class. Moreover, this study provides new references to translators and researchers because it analyzes conversations in virtual space.